2019
DOI: 10.1037/ort0000386
|View full text |Cite
|
Sign up to set email alerts
|

Linking parents’ self-stigma to the adjustment of children with disabilities.

Abstract: This study examined the association of parental self-stigma with child adjustment, and whether parenting self-efficacy and parenting distress mediated the association. Cross-sectional data were collected from 186 families living with kindergarten children identified to have disabilities in Hong Kong, China (mean age = 61.62 months; 76% of them were boys). Using questionnaires, 173 mothers and 112 fathers reported their own self-stigma, parenting self-efficacy, and parenting distress, as well as their children’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 74 publications
(139 reference statements)
3
11
0
Order By: Relevance
“…Kabiyea and Manor-Binyamini (2019) found a negative relationship between stigma and self-efficacy and a positive relationship between stigma and anxiety in parents of adolescents with developmental disabilities. The study of Li et al (2019) is the only one we have found that focuses on the self-stigma of caregivers of children with developmental disabilities. They found that parents’ self-stigma was linked to fewer prosocial behaviors and more externalizing and internalizing behaviors among children, but such links were partially alleviated by parenting self-efficacy.…”
Section: Perception Of Discrimination and Internalization Of Stigmamentioning
confidence: 99%
“…Kabiyea and Manor-Binyamini (2019) found a negative relationship between stigma and self-efficacy and a positive relationship between stigma and anxiety in parents of adolescents with developmental disabilities. The study of Li et al (2019) is the only one we have found that focuses on the self-stigma of caregivers of children with developmental disabilities. They found that parents’ self-stigma was linked to fewer prosocial behaviors and more externalizing and internalizing behaviors among children, but such links were partially alleviated by parenting self-efficacy.…”
Section: Perception Of Discrimination and Internalization Of Stigmamentioning
confidence: 99%
“…In other words, children with SDD with higher importance (High PageRank) do not receive significant more caregiving than children with SDD with lower importance (Low PageRank). Our interpretation involves the caregivers' self-stigma that children with more severe DD are harder to care for than children with MND [68]. This self-stigma might then result in a self-fulfilling prophecy that children with SDD face more problems, which in turn exacerbates negative child outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Some examples of this self-stigma can manifest through caregivers' attitudes towards children with SDD. It has been found that parents and caregivers tend to have reservations towards including children with SDD in education programs [69], with parents tending to view children with disabilities as having lower socioemotional and behavioral skills [68,70]. While, in general, the importance of the child in the family affects the level of caregiving the child receives [62] as explained above, this self-stigma [68] might reduce or override this effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When students leave school underprepared for postsecondary study or for the workplace, educators and schools have commonly been indicted as having failed those students (e.g., Anderson, 2011;DeWeese, 2007;Postal and Roth, 2011). Furthermore, one reason many students with disabilities face challenges may be due in part to secondary special education teachers' feeling unprepared to plan for and deliver transition services (Li et al, 2009). Effective preparations necessitate the provision of training on specific knowledge and competencies often beyond what is included in most special education teacher preparation programs (Anderson et al, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%